EVALUASI METODE PENENTUAN HALF VALUE LAYER (HVL) MENGGUNAKAN MULTI PURPOSE DETECTOR (MPD) BARRACUDA PADA PESAWAT SINAR-X MOBILE - Handini Devi Yunitasari; Evi Setiawati; Choirul Anam (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2014)
The dose received by the patient and the radiographic image quality is determined by the value of the half value layer (HVL). Multi Purpose Detector (MPD) Barracuda, produced by RTI Electronics, Sweden, is a solid state detector that can be used to measure the value of HVL just one exposure. This study was conducted to evaluate the accuracy of measurement of the HVL’s value with single exposure methods using the MPD Barracuda. In this study the value of HVL measurements performed with distance of focus to detector 100 cm, field size of 10x10 cm2 and times- current 12.5 at a voltage of 50 kVp, 60 kVp, 70 kVp, 81 kVp and 90 kVp. HVL measurement for single exposure method conducted without the addition of Al filter. As for comparative used standard methods that use some thickness variation of filters from 0.5 to 5.0 mmAl. In the standard method, determination of HVL values calculated in two ways: interpolation formula and method of graphs. The results showed that the value of HVL using MPD Barracuda with single exposure method produces a lower value than the standard method used multiple filters and HVL calculated by interpolation and graphics.Keywords: Half Value Layer (HVL), Multi Purpose Detector (MPD) Barracuda, X-ray.